2004
DOI: 10.3998/ark.5550190.0005.d03
|View full text |Cite
|
Sign up to set email alerts
|

New steroidal saponins from the sponge Erylus lendenfeldi

Abstract: Our search for biologically active marine natural products has led to the isolation of two new steroidal saponins, eryloside K (2) and eryloside L (3) together with the known antitumor and antifungal glycoside eryloside A (1) from the organic extract of the sponge Erylus lendenfeldi (Geodiidae) collected in the Red Sea. The structures of the new compounds were elucidated on the basis of comprehensive spectral analyses ( 1 H, 13 C, COSY, HMQC, HMBC and TOCSY NMR) as well as GC/MS analysis to infer the absolute … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 15 publications
3
29
0
Order By: Relevance
“…The containing 24(25)-double bond in its aglycone eryloside K ( 45 ) was independently and almost simultaneously isolated by Fouad et al . [ 29 ] at the studies on the same sponge, collected off the Jordan coast in the Gulf of Aqaba, the Red Sea. Eryloside L ( 46 ) was structurally identified by Sandler et al .…”
Section: Tetracyclic Triterpene Glycosidesmentioning
confidence: 99%
“…The containing 24(25)-double bond in its aglycone eryloside K ( 45 ) was independently and almost simultaneously isolated by Fouad et al . [ 29 ] at the studies on the same sponge, collected off the Jordan coast in the Gulf of Aqaba, the Red Sea. Eryloside L ( 46 ) was structurally identified by Sandler et al .…”
Section: Tetracyclic Triterpene Glycosidesmentioning
confidence: 99%
“…Careful comparison of the 1 H and 13 C chemical shift values of similar partial structures within the side chain of 3 with data published for both possible isomers (R & S) for which Mosher esters and NOE experiments have been carried out, revealed that the carbon atom bearing a-configured hydroxyl group and its proton are always shielded by . 3 -6 and 0.38-0.39 ppm, respectively over the b-isomer (Fouad et al 2004;Liu & Abreu 2006;Wang et al 2008;Nakata et al 2009;Sultana & Sultana 2009). This placed the hydroxyl group as (a) and suggested the configuration at C-23 as (S).…”
Section: Resultsmentioning
confidence: 91%
“…Eryloside A ( 118 ) was the first eryloside congener isolated from the Red Sea sponge Erylus lendenfeldi (class Demospongiae; order Choristida; family Geodiidae) [ 107 ]. Twenty eight additional erylosides (A–F, F 1 –F 7 , G–V) have been reported from different species of the genus Erylus including E. goffrilleri [ 109 , 114 ], E. formosus [ 110 , 113 ], E. nobilis [ 111 ], in addition to another collection of E. lendenfeldi [ 112 ].…”
Section: Triterpenes (C 30 )mentioning
confidence: 99%
“…Erylosides K ( 123 ) and L ( 124 ) have been obtained together with 118 from another collection of the Red Sea marine sponge Erylus lendenfeldi [ 112 ]. While 123 was identified as the 24,25-didehydro congener of eryloside A, eryloside L ( 124 ) incorporated a naturally unprecedented 8 α ,9 α -epoxy-4 α -methyl-8,9-secocholesta-7,9(11),14-triene skeleton [ 112 ]. Erylosides A ( 118 ) and K ( 123 ) led to a 50% mortality rate in the brine shrimp assay at a concentration of 0.14 mM.…”
Section: Triterpenes (C 30 )mentioning
confidence: 99%
See 1 more Smart Citation